Improving the quality of learning of specialists in the field of learning “Information security” - D. S. Karpov; A. A. Mikryukov; P. A. Kozyrev (Открытое образование (Москва), 2019)
Purpose of the study.  The aim of the study is to substantiate and develop an approach to improving the quality of training of specialists in the direction of training “Information Security”, based on improving the quality of assimilation of the educational material of the disciplines provided for by the curriculum.Materials and methods.  To achieve this goal, it is proposed to use innovative teaching methods based on the use of modern interactive educational technologies.The study is based on the analysis and use of research materials in the field of the application of pedagogical technologies in the modern educational process, the requirements of the law, which are mandatory when implementing the main educational programs of higher professional education. In preparing the article, the materials obtained by the authors during the planning, preparation, conduct and analysis of laboratory studies with students studying in the direction of training “Information Security” were also used.Results.  The specifics of training specialists in the direction of training “Information Security”, due to the high demands placed on them by employers, as well as the complexity and necessity of solving the problems facing the Russian Federation in the field of ensuring information security, lies in the need for them to obtain, along with fundamental knowledge in the field of information security, knowledge of modern and promising information protection technologies.An important role in improving the quality of training highly qualified specialists who are professionally in demand and capable of self-development is currently played by the application of new approaches to their training based on the use of innovative methods. The proposed approach consists in the development by students of modern and promising information protection technologies using innovative teaching methods during the organization, preparation and conduct of training sessions.One of the main, most important in practical, research aspects, forms of conducting classes in the process of training information security specialists is a laboratory workshop.The proposed approach was tested in the educational process when planning, preparing and conducting laboratory work on the topic “Creating a virtual private network in a virtual environment” in the discipline “Information Security Technology”. The main features of this lesson include the relevance, high technology and practical orientation of the topic of the lesson, as well as its interactivity.The result of applying the proposed approach was an increase in the degree of assimilation, the breadth of coverage of the studied material and, as a result, an increase in the effectiveness of the formation of students’ competencies provided for in the curriculum.Conclusion.  As a result of the research, an approach to improving the quality of training of specialists in the field of training “Information Security” was substantiated and developed.The proposed approach, which consists in the application of innovative interactive teaching methods during the organization, preparation and conduct of training on relevant, high-tech topics of applied importance, was implemented in practice when students learn the discipline “Information Security Technology”, which allowed to improve the quality of assimilation educational material of the discipline and, ultimately, to improve the quality of training of specialists in the direction of training “Information Security”.